2022
DOI: 10.1007/s10646-022-02610-x
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal effects of five common herbicides on the wolf spider, Pardosa milvina (Araneae: Lycosidae)

Abstract: We tested lethal and sublethal effects of ve commonly applied herbicides on the agrobiont wolf spider Pardosa milvina. Pardosa were collected from two agricultural elds; one kept under continuous crop rotation and sprayed for over twenty years, the other had no pesticide application for the last twelve years. Male and female Pardosa from each site were exposed to one of seven herbicide treatments (atrazine, glyphosate, mesotrione, S-metolachlor, rimsulfuron, a combination of all ve herbicides, or a distilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This may be due to differences between species. While exposure levels from [176] are difficult to compare because of different experimental procedures (5.04 µg/cm 2 at 30.34%), they appear to be comparable among the other three studies (12 g/L [174], 14.4 g/L [152] and 15 mL/L [175]).…”
Section: Reproductive and Maternal Behaviormentioning
confidence: 50%
See 3 more Smart Citations
“…This may be due to differences between species. While exposure levels from [176] are difficult to compare because of different experimental procedures (5.04 µg/cm 2 at 30.34%), they appear to be comparable among the other three studies (12 g/L [174], 14.4 g/L [152] and 15 mL/L [175]).…”
Section: Reproductive and Maternal Behaviormentioning
confidence: 50%
“…Male agrobiont spiders and beetles exhibit similar courtship behaviors and experience similar success rate and duration of mating regardless of whether the surface they were on contained GBH residues [152]. A similar study on wolf spiders and glyphosate showed no significant effect on courtship or sexual behavior in either sex of the spider [176]. This may be due to differences between species.…”
Section: Reproductive and Maternal Behaviormentioning
confidence: 88%
See 2 more Smart Citations